MODEL RELASI SAINS-AGAMA JOHN HAUGHT: RELEVANSINYA DALAM PENDIDIKAN ISLAM - Imroatul Hasanah; Daris Salama Ulin Nuha; Halimatus Sa’diyah; Asnawan (As-Sulthan Journal of Education, 2026)
This article explores John Haught’s model of the science–religion relationship, comprising four main approaches: conflict, contrast, contact, and confirmation. Using library research and descriptive–comparative analysis, the study examines how Haught’s framework offers a dialogical paradigm that enables constructive integration between modern science and religious teachings. The findings reveal that Haught’s “contact” and “confirmation” models hold significant relevance for the development of Islamic education, particularly in designing curricula that respond to scientific progress while maintaining theological integrity. Haught’s thought helps bridge the dichotomy between science and religion, fosters a religiously grounded scientific attitude, and promotes learning that is more critical, open, and holistic. Thus, Haught’s model of the science–religion relationship provides an epistemological foundation for strengthening the integration of knowledge within contemporary Islamic education.